High Strength Conductors and Structural Materials for High Field Magnets. Issue 17 (2016) - Han, Ke; Niu, Rongmei; Lu, Jun; Toplosky, Vince
ABSTRACT: One important approach to increasing High magnetic fields (HMF) beyond what is now possible is to improve the properties of various composite materials used as both conductors and structural support. Typical conductors for high field magnets are Cu-based metal-metal composites. To achieve high mechanical strength, these composites are fabricated by cold deformation, which introduces high densities of interfaces along with lattice distortions. During the operation of a magnet, mechanical load, high magnetic field, extreme temperatures and other stressors are imposed on the materials, causing them to be further "processed". The composite conductors in a magnet, for example, may undergo high temperatures, which reduce lattice distortions or soften the material. At the same time, HMF may increase lattice distortion, leading to a complex change in interface characteristics. Both the mechanical properties of the conductors, like the tensile and yield strength, and the electric conductivity of the composites are closely connected to changes in lattice distortion and interface density. Understanding these changes helps us to assure that materials can operate in optimized conditions during most of magnets' service life. Maximizing service life is critical, given the high cost of building and operating high field magnets. The goal of this paper is to 1) show our understanding of changes that occur in the properties of selected materials during the fabrication and under HMF and 2) to discuss how those changes relate to the microstructure of these materials and consequently to the service life of high field magnets.